Effects of early introduction of solid foods on nutrient intake in preterm infants during their 1st year of life: a secondary outcome analysis of a prospective, randomized intervention study - Gsoellpointner, Melanie; Eibensteiner, Fabian; Thanhaeuser, Margarita; Ristl, Robin; Jilma, Bernd; Berger, Angelika; Haiden, Nadja (Frontiers in Nutrition, 2023)
Very low birth weight (VLBW) infants have higher nutritional needs even after discharge but data concerning current nutrient intakes under different timepoints of introduction of solid foods and whether dietary reference values are met are scarce. This secondary analysis of a prospective, two-arm interventional study in 177 VLBW infants investigates dietary intake comparing early and late (early: 10–12th, late: 16–18th week corrected age) introduction of standardized complementary food during the first year of life. Nutritional intake was assessed using self-reported monthly 3-day dietary records from 3 until 12 months corrected for term. The timepoint of introduction of solid foods did not influence nutrient intake, but early introduction of solids tended towards a higher proportional intake of protein and carbohydrates and a lower intake of fat (% of total energy) during the first year of life corrected for term. Results of this study indicate that this standardized feeding concept was sufficient in zinc, calcium, and phosphorus intake. However, dietary iron and vitamin D intakes did not meet recommendations, thus, prolonged iron supplementation beyond the introduction of meat and vitamin D supplementation at least until 12 months corrected for term should be considered.